A Dilatometric Study of Graphite Electrodes during Cycling with X-ray Computed Tomography. Issue 1 (7th January 2021) - Michael, H.; Iacoviello, F.; Heenan, T. M. M.; Llewellyn, A.; Weaving, J. S.; Jervis, R.; Brett, D. J. L.; Shearing, P. R.
Abstract : Graphite is the most commonly used anode material in commercial lithium-ion batteries (LiBs). Understanding the mechanisms driving the dimensional changes of graphite can pave the way to methods for inhibiting degradation pathways and possibly predict electrochemical performance loss. In this study, correlative microscopy tools were used alongside electrochemical dilatometry (ECD) to provide new insights into the dimensional changes during galvanostatic cycling. X-ray computed tomography (CT) provided a morphological perspective of the cycled electrode so that the effects of dilation and contraction on effective diffusivity and electrode pore phase volume fraction could be examined. During the first cycle, the graphite electrode underwent thickness changes close to 9% after lithiation and, moreover, it did not return to its initial thickness after subsequent delithiation. The irreversible dilation increased over subsequent cycles. It is suggested the primary reason for this dilation is electrode delamination. This is supported by the finding that the electrode porosity remained mostly unchanged during cycling, as revealed by X-ray CT.